PERAN MAJELIS PENGAWAS DAERAH DALAM PERLINDUNGAN HUKUM TERHADAP NOTARIS YANG MENGHADAPI MASALAH HUKUM DI JAKARTA TIMUR - , Ghessa Nashara Tasya; , Sigid Riyanto, SH., M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to determine the factors that cause the Law issues faced by Notary and the Role of Regional Supervisory Council (MPD) in East Jakarta in protection to the troubled notary. This study is an empirical juridical research that illustrates the reality that happening in the community, and then analyzed it by comparing the normative value of the legislation and the reality on the field. The data obtained in this study is secondary and primary data. Secondary data are primary legal materials, and secondary legal materials obtained from various libraries, Internet sites, journals and magazines, while the primary data obtained through interviews with respondents who meet the criteria set by the researcher e.g. Regional Supervisory Council (MPD) of East Jakarta, some senior Notaries, and finally the data analyzed qualitatively. There are two conclusions results (2), namely 1. The factor causing the Notary get law issues are their Violation or disobedience to execute the provisions of the UUJN Code and ethical provisions